On augment-less NPs in Xhosa and de NPs in French - Taraldsen, Knut Tarald (Stellenbosch Papers in Linguistics Plus, 2019)
Augment-less NPs in Xhosa and de NPs like de chevaux ‘of horses’ have strikingly similar properties. It seems that the properties of de NPs reflect the absence of the definite article les which combines with de to form the so-called partitive article des chevaux ‘some horses’. Taking the Xhosa augment to be similar (though not identical) to the French definite article, we account for the observed similarities between augment-less NPs and French de NPs.